The Applicability of ILO’s Employment Relationship Recommendation No. 198 in Shaping Universal Approaches to Distinguish Work Relationships in Lithuania and Internationally - Lauschke, Hans (Teisė, 2025)
Nearly two decades have passed since the International Labour Organization (ILO) adopted the Employment Relationship Recommendation, 2006 (No. 198). This article explores the relevance and potential influence of the Recommendation, and, in particular, Sections 12 and 13 of its Chapter II on national work relationships. It investigates whether the Recommendation can assist in assessing the nature of employment relationships and new forms of work in Lithuania and internationally. Through an analysis of the documents and reports underpinning the Recommendation, the article concludes that, while it offers formal and methodical proposals, there is considerable room for misinterpretation regarding its significance for the content of national employment relationship concepts.